Areas of vascular plants endemism in the Monte desert (Argentina) - Elías, Gabriela del Valle (2016)
In order to identify concordant distributions of endemic vascular plants in the Monte desert, we analyzed the distributional data of 180 species endemic to the Monte desert with the optimality criterion implemented in the program VNDM. We detected 13 partially overlapping areas of vascular plant endemism.The main areas of endemism are distributed from north to south associated with the mountainous region of the Precordillera of the Andes towards the west of the study region. These main areas correspond to environments with important variation in elevation and aridity, whereas minor areas correspond to patches of the steppe vegetation towards the east of the study region. We also obtained extensive areas covering much of the Monte desert, coincident with the two classical biogeographic units proposed. In agreement with the general arid climate of the Monte, most of the endemic flora inhabits arid and/or semiarid environments.